Guidelines and procedures manual (CCS GeorgetownGY, 1994)
Establishes procedures and guidelines which will allow the Caribbean Community Secretariat staff and others working on their behalf to perform their duties/responsibilities more economically, efficiently and in a transparent manner. Facilitates the control and accountability of CRISP as a project. Explains the key stages of a project life cycle.
DC